Metal Sulfide/Carbon Composite Fibers as Anode Materials for Lithium Ion Batteries. (19th June 2018) - Lopez, Jorge; Villarreal, Jahaziel; Cantu, Jesus; Parsons, Jason; Alcoutlabi, Mataz
Abstract : In this study, Forcespinning is used to produce TiS2 /carbon composite fibers for lithium ion battery anodes. The use of a 2-D layered structure of TiS2 nanoparticles in the carbon fiber matrix can greatly accommodate more Li ions between the layers leading to increased specific capacity, improved stability and good electrochemical performance of the anode after prolonged charge/ discharge cycles. The TiS2 /C composite fiber anodes delivered a discharge and charge capacities at the first cycle of 900 mAhg -1 and 600 mAhg -1, respectively. Some of the TiS2 nanoparticles turned into a 2-D layered structure of TiO2 nanoparticles after the oxidation process in air environment. The TiS2 /C composite fibers show an improvement in the electrochemical performance over the commercially graphite anodes of 372 mAhg -1 . When was used as anode for LIBs, the layered structure of TiO2 composite fibers showed charge capacity of 250 mAhg -1 after 100 cycles at 50 mAg -1 .